Asset Allocation in Different Macroeconomic Environments - Johansson,Daniel; Schou Kongstad,Andreas (2014)
Understanding how asset classes and systematic strategies behave and perform during different macroeconomic environments is essential for an efficient asset allocation process. The aim of this thesis is to find a method to systematize the current understanding of the relationship between asset performance and environments. We will present a way to define different macroeconomic environments, assess the forecast predictability of the Composite Leading Indicator (CLI), develop a strength indicator to foresee turning points and in the end be able to recommend a portfolio allocation strategy based on our findings. Our results, as well as earlier research, indicate that it is possible to forecast the CLI with good performance. Furthermore, our results have shown that we are able to take long/short positions in order to receive excess return in various asset classes based on the macroeconomic environments we have defined.
Keywords: Composite Leading Indicator; CLI; Asset Allocation; Vector Autoregressive Model; Forecast